PENGARUH KECANGGIHAN TEKNOLOGI INFORMASI, PARTISIPASI MANAJEMEN, BUDAYA ORGANISASI DAN KEPUASAN PENGGUNA PADA EFEKTIVITAS SISTEM INFORMASI AKUNTANSI BANK PERKREDITAN RAKYAT DI KABUPATEN BADUNG - Dwitrayani, Made Christin; Widanaputra, A.A. G.P; Putri, IGAM Asri Dwija (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
The research aims to find out the effect of technological sophistication, management participation, organizational culture, and user’s satisfaction on the effectiveness of accounting information system at Rural Credit Bank in Badung Regency. Population in this study is Rural Credit Banks in Badung Regency. Sample in this study is Rural Credit Banks which have total asset value above ten billion rupiah, so that sample in this study is as many as 36 companies. According to the regulation of Bank of Indonesia, Rural Credit Bank has two directors so that total respondents in this research are 72 persons. Analysis technique being used is regression multiple analysis technique. Based on the result of analysis it is known that the sophistication of information technology affects positively on the effectiveness of accounting information system. System which has good informational sophistication will help the company to generate fast and accurate information for effective decision. Management participation affects positively on the effectiveness of accounting information system. Keywords : Technological Sophistication, Management Participation, Organizational Culture, User’s Satisfaction, Effectiveness of Accounting Information System
Keywords: Technological Sophistication, Management Participation, Organizational Culture, User’s Satisfaction, Effectiveness of Accounting Information System